The blessings of business : how corporations shaped conservative Christianity - Grem, Darren E. (New York : Oxford University Press, 2016)
"Tells the largely forgotten story of the historical ties between conservative Protestants and corporate America; shows how business executives have been crucial to the growth of modern evangelicalism; explains how evangelicals attached their social and religious aspirations to American corporate culture and the private sector."--Https://global.oup.com.
Part I. How big businessmen shaped conservative evangelicalism. Fundamentalist fronts: Herbert J. Taylor, businessmen, and the "revival" of conservative evangelicalism -- Corporate convictions: Billy Graham, big business, and the new evangelicalism -- Corporate crusades: markets, missions, and R.G. LeTourneau's cold war -- Part II. How conservative evangelicalism became big business. Marketplace missions: Chick-fil-A and the evangelical business sector -- Culture industries: Heritage USA and the corporatization of evangelical culture -- Free-market faith: Zig Ziglar and the business of evangelical culture war.
Includes index.
Includes bibliographical references and index.
Keywords: United States -- Church history -- 20th century; Business -- Religious aspects -- Christianity; Conservatism -- Religious aspects -- Christianity; Conservatism -- United States -- History -- 20th century; Evangelicalism -- United States -- History -- 20th century